Staphylococcus aureus-specific IgA antibody in milk suppresses the multiplication of S. aureus in infected bovine udder - Yuya Nagasawa (BMC Veterinary Research, 2019)
Abstract Background Bovine mastitis caused by Staphylococcus aureus (S. aureus) is extremely difficult to control and new methods for its prevention and management are required. Nasal vaccines may prevent initial bovine mastitis infection caused by S. aureus. However, limited information is available regarding induction of mucosal immune response through nasal immunization with antigen and its suppression of S. aureus multiplication during bovine mastitis. This study sought to investigate whether induction of immunoglobulin A (IgA) in milk by nasal immunization could suppress multiplication of S. aureus in the bovine udder. Results Nasal immunization with formalin-killed S. aureus conjugated with a cationic cholesteryl-group-bearing pullulan-nanogel was performed. Anti-S. aureus-specific IgA antibodies were significantly more abundant in the milk of immunized cows than in non-immunized animals (P < 0.05). S. aureus counts in the quarter were negative in both non-immunized and nasal-immunized cows 1 week after mock infusion. In S. aureus-infused quarters, S. aureus multiplication was significantly suppressed in immunized compared with non-immunized cows (P < 0.05). Furthermore, a significant negative correlation was found between S. aureus-specific IgA antibodies and S. aureus counts in infused quarters of both non-immunized and nasal-immunized cows (r = − 0.811, P < 0.01). Conclusion In conclusion, the present study demonstrates that S. aureus-specific IgA antibodies in milk successfully suppressed the multiplication of S. aureus in infected bovine udders. Although the exact mechanism explaining such suppressive effect remains to be elucidated, nasal vaccines that can induce humoral immunity may help prevent initial infection with S. aureus and the onset of bovine mastitis.